Move hands like clouds : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Design, Massey University, Wellington, New Zealand - Whiterod, Lee (Massey University, 2012)
This thesis describes the processes and outcomes of my Master of Design Project, Move hands like clouds. It explores the connections between social sustainability, design, somaesthetics and Taoist Tai Chi. The designed outcome, a film, expresses the inclusive design of Taoist Tai Chi, its group activity within a community and its priority of focus on the internal origins and stance of its practice. It uses LED light drawings to trace the movements of multiple practitioners. It is an experience design response to the belief that we experience the world and our place in it through an integrated mind, body and spirit – all the senses – the rational and the intuitive. This stance is shared by the philosophies that underpin social sustainability, somaesthetics, Taoist Tai Chi, and design for sustainability. Mindful attitudes and behaviours with a focus on the wellbeing of the individual and the community is integral to these disciplines and to my film.
Keywords: Tai chi; Somaesthetics; Social sustainability; Abstract film; Mind, body, spirit